Respuesta :
ANSWER
[tex]25 {x}^{2} - 16 =( {5x - 4})(5x + 4)[/tex]
EXPLANATION
We want to factor the expression,
[tex]25 {x}^{2} - 16[/tex]
We can rewrite the expression as
[tex]25 {x}^{2} - 16 = ({5x})^{2} - {4}^{2} [/tex]
The expression is now a difference of two squares,
Recall that,
[tex] {a}^{2} - {b}^{2} = (a - b)(a + b)[/tex]
The expression now becomes;
[tex]25 {x}^{2} - 16 =( {5x - 4})(5x + 4)[/tex]
Therefore the correct answer is option A.
[tex]25 {x}^{2} - 16 =( {5x - 4})(5x + 4)[/tex]
EXPLANATION
We want to factor the expression,
[tex]25 {x}^{2} - 16[/tex]
We can rewrite the expression as
[tex]25 {x}^{2} - 16 = ({5x})^{2} - {4}^{2} [/tex]
The expression is now a difference of two squares,
Recall that,
[tex] {a}^{2} - {b}^{2} = (a - b)(a + b)[/tex]
The expression now becomes;
[tex]25 {x}^{2} - 16 =( {5x - 4})(5x + 4)[/tex]
Therefore the correct answer is option A.